Open educational resources third party creators [electronic resource] - RMIT (Royal Melbourne Institute of Technology). University Library; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (Melbourne RMIT University Library, 2019)
Open Educational Resources (OERs) are any type of educational materials that are in the public domain. They are published under open licenses (i.e Creative Commons) that specify how materials can be used, reused, adapted, shared and modified according to specific needs. They can include textbooks, lecture notes, syllabi, assignments and tests. Open Education resources produced by non-RMIT creators.
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Open education; Education, Higher; General education -- Aids and devices -- Open educational resources; College teaching -- Electronic textbooks -- Open educational resources; Education, Higher -- Electronic textbooks -- Open educational resources